The Capacity of Islamic Education Teachers as al-Muaddib: A Systematic Review - Salinda Sahrin, Mohamad Zulkifli Abdul Ghani (International Journal of Advanced Science and Technology, 2019)
High-quality Islamic Education teachers (GPI) play the role of muallim, mudarris, murabbi, muaddib and mursyid. However, recent studies on the capacity of Islamic Education teachers as al-muaddib have not been systematically studied. Therefore, this article will discuss the role of Islamic Education teachers as al-muaddib more systematically using the PRISMA Statement of Review method. The researcher has identified two related studies in the Scopus and Web of Sciences databases and 13 articles in Google Scholar and Mendeley. Analysis of research findings using Atlas.ti 8 software. Further review of this article found that the concept of ta’dib in education is very much in line with the role of Islamic Education teachers as al-muaddib in ensuring student morals and manners through the attitude and example of the teacher himself or herself. Therefore, Islamic Education teachers should have the qualities of a genuine muaddib as one of the efforts to educate students to practice good manners. Keywords: systematic review, Islamic education teachers, roles, ta’dib concepts, Islamic scholars